“When he is around, I’ll take the PrEP, but when he is not, I will not take PrEP”: key influences on PrEP use decisions among women attending family planning clinics in Kenya - Ogello, Vallery; Beima-Sofie, Kristin; Urusaro, Sandra; Awuor, Mercy; Dollah, Annabell; Atieno, Winnie; Wandera, Cynthia; Matemo, Daniel; Morton, Jennifer F.; Ngure, Kenneth; Kinuthia, John; Mugwanya, Kenneth K. (Frontiers in Medicine, 2025)
BackgroundWomen of childbearing age in sub-Saharan Africa (SSA) face a disproportionately high risk of HIV acquisition. Although oral PrEP has been universally scaled up for individuals at significant risk of HIV, its uptake and sustained use remain suboptimal. Understanding PrEP use decisions offers insights into context-specific barriers and facilitators to its utilization.MethodsFrom September to November 2023, we conducted a qualitative study nested in a larger prospective, open-label clinical trial (FP-Plus). We conducted in-depth interviews (IDIs) with younger women (ages 15–24) and older women (ages ≥25) who declined, delayed, discontinued, or restarted PrEP during the study. IDIs were conducted at two FP clinics by trained Kenyan social scientists and were audio recorded, translated, and transcribed. We analyzed data using inductive and deductive thematic analysis through the lens of the theory of planned behavior (TPB) to explore experiences, beliefs, and rationale among women who made various PrEP decisions.ResultsWe interviewed 64 women, including 40 younger women and 24 older women, all of whom declined, delayed, discontinued, or restarted PrEP (n = 16 women/category). The median age of these women was 24 years (IQR, 23–30). The majority of participants (86%, 55/64) were using family planning methods, primarily injectables (42%, 23/64). PrEP discontinuation or restart was primarily influenced by changes in HIV risk dynamics. Agency and perceived HIV risk were pivotal factors in PrEP use decisions, shaping participants’ ability to practice effective prevention adherence (TPB: perceived behavioral control). Women who declined PrEP cited a lack of autonomy, partner influence, and insufficient information (TPB: social and subjective norms). Low self-efficacy influenced decisions to delay or decline PrEP (TPB: behavioral beliefs and attitudes). In addition, challenges with PrEP pill size, taste, and texture were perceived as barriers to swallowing pills among all groups of women. Participants expressed a preference for alternative PrEP formulations, such as injectable PrEP, due to perceived ease of use, privacy, and potential to support adherence.ConclusionPrEP discontinuation and restart cycles largely reflected changes in HIV risk. Women who decline or delay PrEP may benefit from personalized support to improve their autonomy, recognizing that HIV risk persists during periods of PrEP delay.